Optical characterization of pure vegetable oils and their biodiesels using Raman spectroscopy. (10th March 2016) - Firdous, S; Anwar, S; Waheed, A; Maraj, M
Abstract: Great concern regarding energy resources and environmental polution has increased interest in the study of alternative sources of energy. Biodiesels as an alternative fuel provide a suitable diesel oil substitute for internal combustion engines. The Raman spectra of pure biodiesels of soybean oil, olive oil, coconut oil, animal fats, and petroleum diesel are optically characterized for quality and biofuel as an alternative fuel. The most significant spectral differences are observed in the frequency range around 1457 cm −1 for pure petroleum diesel, 1427 for fats biodiesel, 1670 cm −1 for pure soybean oil, 1461 cm −1 for soybean oil based biodiesel, 1670 cm −1 for pure olive oil, 1666 cm −1 for olive oil based biodiesel, 1461 cm −1 for pure coconut oil, and 1460 cm −1 for coconut oil based biodiesel, which is used for the analysis of the phase composition of oils. A diode pump solid-state laser with a 532 nm wavelength is used as an illuminating light. It is demonstrated that the peak positions and relative intensities of the vibrations of the oils can be used to identify the biodiesel quality for being used as biofuel.